Sergei Eisenstein in the Proletkult - Biggart John; Bulgakowa Oksana (Cultural Science)
This article examines some of the theoretical issues that exercised Sergei Eisenstein during the years 1920–1924 when he worked in the Russian Proletarian Cultural-Educational Organization (Proletkult), of which Aleksandr Bogdanov was one of the founders. We ask how far Eisenstein was influenced by Marxism in general and by the ideas of Bogdanov in particular, and explain his exit from the Proletkult in terms of the unacceptability of his theory and practice of theatre and film to the Chairman of the Proletkult, Valeriyan Pletnëv. During these years the Agitprop Department of the Central Committee of the Communist Party, at Lenin’s behest, was taking steps to reduce the scope of activities of the Proletkult, discredit Bogdanov as a thinker, and exclude him from politics.